Cinderella Syndrome of Working Women in Cyber Literature - Eva Fatimah; Imas Istiani (Universitas Dian Nuswantoro, 2020)
Abstract. Cyber literature has been academically recognized in literary studies through multiple research studies. Cyber literature is manifested in various cyberspace, both maintained individually and professionally. Writing platforms on the internet, such as Wattpad, have been widely used. They provide space for writers and engage readers to create online writing communities. One of the most popular genres found in cyber literature is romance chick-lit, in which most main characters are working women. Although most protagonists are working women who are financially independent, they still search for men who have higher positions, social levels, and financial stability. They wish that such men will find and save them, referred to by Colette Dowling as Cinderella complex. The study investigates the Cinderella complex's indications on female protagonists in two Wattpad chick lit works: 1) Furious Boss & Naughty Secretary, and 2) Ex-lovers but Married. The indications of Cinderella Complex were shown through 1) the wish to be saved, 2) the girl-child lives on, 3) the achievement gap, 4) the intimations of helplessness, and 5) the blind devotion.Keywords: Cinderella complex; cyber literature, WattpadAbstrak. Sastra cyber sudah diperhitungkan sebagai bagian dari studi sastra secara akademik melalui berbagai penelitian yang sudah dilakukan. Sastra cyber terwujud di dalam berbagai ruang cyber, baik itu dijalankan secara individual maupun profesional. Platform menulis pada internet seperti Wattpad sudah marak digunakan sebagai tempat berkarya bagi penulis serta menarik perhatian pembaca untuk menciptkana suatu komunitas menulis secara online. Salah satu genre populer pada sastra cyber adalah chicklit romantis yang mana karakter utamanya adalah wanita pekerja. Meskipun protagonis wanita merupakan wanita pekerja yang independen secara finansial, mereka masih mengharapkan pasangan yang berada di posisi, tingkat sosial dan kestabilan finansial yang lebih besar dari mereka. Studi ini bertujuan untuk mencari indikasi adanya Cinderella complex pada karakter protagonis perempuan melalui dua karya chicklit di Wattpad, yaitu: 1) Furious Boss & Naughty Secretary, dan 2) Mantan Tapi Menikah. Indikasi Cinderella complex yang ditemukan adalah 1) keinginan untuk diselamatkan, 2) gadis-kecil yang hidup di dalam diri, 3) kesenjangan prestasi, 4) tanda ketidakmampuan, dan 5) kepatuhan yang buta.Kata kunci: Cinderella complex; sastra cyber, Wattpad